2022
DOI: 10.1002/mar.21696
|View full text |Cite
|
Sign up to set email alerts
|

Temporary or permanent social media post? The impact of product type

Abstract: Consumers share various content about material and experiential products on social media for short-term via temporary posts or long-term via permanent posts. Based on memory protection and hedonic adaptation theories, this study investigates whether product type determines how long consumers display their products on social media. We suggest experiential products elicit more proactive nostalgia-the desire to have a permanent record of a current episode to remember and relive it in the future-than material prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…This echoes Anlamlier and Ulu (2022), who found that consumers prefer to share experiential consumption permanently on social media due to proactive nostalgia.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…This echoes Anlamlier and Ulu (2022), who found that consumers prefer to share experiential consumption permanently on social media due to proactive nostalgia.…”
Section: Resultssupporting
confidence: 62%
“…I think on Instagram specifically, I'm more interested in sharing it so that I can look at it later in an organized way. (B14)This echoesAnlamlier and Ulu (2022), who found that consumers prefer to share experiential consumption permanently on social media due to proactive nostalgia.Lastly, extrinsic motivations constituted another major motivator of travel bragging. Extrinsic motivations are driven by separable outcomes such as external rewards or punishments(Ryan & Deci, 2000).…”
mentioning
confidence: 75%
“…As a commonly experienced emotion, nostalgia can be triggered by a number of factors such as feelings of distress (Routledge et al, 2013), experiential gifts (Puente‐Díaz & Cavazos‐Arroyo, 2021) as well as products (Anlamlier & Ulu, 2022), and loneliness (Wildschut et al, 2006). Recent studies suggest that aversive and threatening events such as coronavirus disease 2019 (COVID‐19) severity (Xia et al, 2021) and disease threat (Barauskaitė et al, 2022) can also evoke feelings of nostalgia, which are effective in coping with threats such as stress, anxiety, and loneliness.…”
Section: Introductionmentioning
confidence: 99%